The Role of Guidance Counsellors in Curbing the Menace of Drug Abuse among Secondary School Students in Nigeria - UWADIA, John Chukwuewene; FADIPE, Rasaq Abimbola; KAYODE, Olajide Charles; OLUWWOLE, Phebe Blessing (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
Drug Abuse is a global problem deviling many countries in the world and the rate at which this problem is spreading calls for urgent attention to prevent the situation from getting out of control, particularly among secondary school students in Nigeria. Many of these students engaged in drug abuse out of frustration, poverty, curiosity, lack of parental supervision, lack of guidance and counselling, negative peer influence, and social media influence. The use of marijuana, tramadol, alcohol, tobacco, cocaine, cough syrup and other drugs have become a common practice among students. The paper therefore focuses on the role of guidance counsellors in curbing the menace of drug abuse among secondary school students. It also covers a review of relevant literature on warning signs of drug abuse, drugs commonly abused in schools, counselling theories on drug abuse, causes of drug abuse and its effects among secondary school students. The paper suggested that drug abuse counselling should be an integral part of school curriculum; a method of management which focuses on specific problems arising from the abuse of drug. Counsellors should be equipped with adequate skills and strategies to handle students with behavioural problems in school; and they should always organise lectures, rallies, seminars and film shows for students on the adverse effects and preventive measures on drug abuse.